Deciphering Precise Gene Transcriptional Expression Using gwINTACT in Tomato - Chu, Yiyang; Gong, Jiachen; Wu, Peiwen; Liu, Ye; Du, Yinglin; Ma, Lili; Fu, Daqi; Zhu, Hongliang; Qu, Guiqin; Zhu, Benzhong (Frontiers in Plant Science, 2022)
Functional gene transcription mainly occurs in the nucleus and has a significant role in plant physiology. Isolation of nuclei tagged in specific cell type (INTACT) technique provides an efficient and stable nucleus purification method to investigate the dynamic changes of nuclear gene transcriptional expression. However, the application of traditional INTACT in plants is still limited to seedlings or root cells because of severe chloroplast pollution. Here, we propose a newly designed and simplified INTACT based on mas-eGFP-SlWIP2 (gwINTACT) for nuclear purification in tomato (Solanum Lycopersicum) leaves, flowers, and fruits for the first time. The yield of the nucleus purified using gwINTACT from transgenic tomato leaves was doubled compared with using traditional INTACT procedure, and accompanied by more than 95% removal of chloroplasts. Relative gene expression of ethylene-related genes with ethylene treatment was re-evaluated in gwINTACT leaves to reveal more different results from the traditional gene expression assay based on total RNA. Therefore, establishing the gwINTACT system in this study facilitates the precise deciphering of the transcriptional status in various tomato tissues, which lays the foundation for the further experimental study of nucleus-related molecular regulation on fruit ripening such as ChIP-seq and ATAC-seq.